2023
DOI: 10.1108/ijsi-08-2023-0068
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical analysis of free vibrations of piezoelectric circular plate reinforced with boron nitride

Mohammad Hadi Moradi,
Mehdi Ranjbar-Roeintan

Abstract: PurposeThe purpose of this research is to extract the natural frequencies of a circular plate containing a central hole reinforced with boron nitride nanotubes (BNNTs) and containing piezoelectric layers.Design/methodology/approachA unit cell shall be taken into account for the simulation of BNNT's volume fraction. A rectangular micromechanical model is used to obtain the mechanical properties of unit cell of piezoelectric fiber-reinforced composite (PFRC). The three-dimensional (3D) elasticity method is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…You et al [39] reported the piezoelectric effect on the vibration of carbon and boron nitride coaxial heteronanotubes. Moradi and Ranjbar-Roeintan [40] analyzed the vibration of piezoelectric circular plate reinforced with boron nitride. Zhang [41] conducted the vibration of BN nanotubes affected by the Piezoelectric effects, he obtained the relationship between the resonance frequency of BN nanotube and external electric fields intensity.…”
Section: Introductionmentioning
confidence: 99%
“…You et al [39] reported the piezoelectric effect on the vibration of carbon and boron nitride coaxial heteronanotubes. Moradi and Ranjbar-Roeintan [40] analyzed the vibration of piezoelectric circular plate reinforced with boron nitride. Zhang [41] conducted the vibration of BN nanotubes affected by the Piezoelectric effects, he obtained the relationship between the resonance frequency of BN nanotube and external electric fields intensity.…”
Section: Introductionmentioning
confidence: 99%